Consumption of food supplements for practitioners physical exercise in academies noble neighborhoods in Recife - Santos, Helania Dantas (2013)
The practice of physical activities consolidated in much of the population in the last decade the market has grown along side nutritional supplements is for aesthetic reasons or to improve some aspect of physical performance. In order to identify the prevalence of the use of nutritional supplements by practitioners of exercise gyms in affluent neighborhoods of Recife / PE and the factors associated with use were assessed 59 individuals of both genders, attending three gyms in the noble neighborhoods city trough a questionnaire. The results show that the level of use of nutritional supplements is 94.9% of the women's group which reaches 51.8% use against the group of men 41.2%, the main reasons are possible improvements in training 37%, products being mentioned among the most protein supplements with 31% indicating the main source of friends 37%, followed by 27% instructors. The search for factors that may enhance performance is increasing, coupled with the growing presence of dietary supplements in the academies. It covers both sexes and in order to increase muscle mass individuals resort protein concentrates mainly in the hope of possible improvements in trainingor cosmetic changes. This search for a quick response occurs without the prescription of trained professionals showing the need for a specialist to work in local gyms or exercise that practice and provides recommendations and clarifications on the subjectand reducing the health risks of these individuals.